Nams Structures it Find of Al- Quran: (Example Takes News) - الفحام صفاء توفيق كاظم صادق (Al-Adab Journal, 2019)
The research in include on structure it finds verbs and letters event this structure inter this clear fromit continu happen un old time cut and continu adverb or cross to future which other verb mean wgich was comeing and also become to stay any way. But stay copy this verb without other verbs special event as this structure copy verbs it copys with letters it does with many meaning copys open cross type which finds emphasis over and cause which other meaning declare through research. Might agri this work in Al- Quran text which include researcher news and older stories also because of are strongest location influence modestiy seeing.